2021
DOI: 10.3390/ijerph18158145
|View full text |Cite
|
Sign up to set email alerts
|

‘Improving Health through Reducing Stress’: Parents’ Priorities in the Participatory Development of a Multilevel Family Health Programme in a Low-Income Neighbourhood in The Netherlands

Abstract: In order to reduce health inequities, a socio-ecological approach and community engagement are needed to develop sustained interventions with a positive effect on the health of disadvantaged groups. This qualitative study was part of the development phase of a community health promotion programme. The study aimed to provide insight into the perceptions of parents in a disadvantaged neighbourhood about health, and their priorities for the community health programme. It also described the process of integrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Zika is a complex, unusual disease that demanded a multi-faceted response of vector control and improvements in public health access in Brazil [ 3 , 36 , 37 , 38 ]. Participatory policymaking institutions, such as environmental sanitation councils, enhanced this response in municipalities that used them by incorporating the public and civil society into the mosquito abatement, disease surveillance, and public health education efforts [ 18 , 19 , 20 , 25 ]. In general, our evidence suggests that promoting participatory institutions in Brazil and around the world may be justified to improve governance and public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zika is a complex, unusual disease that demanded a multi-faceted response of vector control and improvements in public health access in Brazil [ 3 , 36 , 37 , 38 ]. Participatory policymaking institutions, such as environmental sanitation councils, enhanced this response in municipalities that used them by incorporating the public and civil society into the mosquito abatement, disease surveillance, and public health education efforts [ 18 , 19 , 20 , 25 ]. In general, our evidence suggests that promoting participatory institutions in Brazil and around the world may be justified to improve governance and public health.…”
Section: Discussionmentioning
confidence: 99%
“…Do local democratic institutions improve public health performance? Which ones and in what ways [ 7 , 18 , 19 , 20 ]? How governments answer these questions will inform healthcare and development policies that affect the lives of billions of people around the world.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a longitudinal study in South Korea followed mothers from their child's birth until age 4; maternal stress was highest when the child was 2 years old, and maternal stress throughout the study period was inversely related to the presence of neighborhood features like daycare centers. In a recent qualitative study, parents from a low-income neighborhood proposed that the community address chronic stress through reducing personal financial stress, ensuring safe places for their children to play, and liaising with authorities [21 ▪ ]. Immigrant and adolescent parents, as we explore soon, are especially impacted by this SDOH.…”
Section: Introductionmentioning
confidence: 98%
“…People living in socioeconomic insecurity may have needs that are more salient for their health than striving for a healthy lifestyle [ 11 13 ]. Wink [ 14 ] found that priorities of those in socioeconomic insecurity were mainly related to reducing chronic stress by addressing what according to Maslow’s hierarchy of needs can be considered as basic needs [ 15 ], including financial security, housing, and safety. This has been acknowledged by other qualitative work among vulnerable populations in the Netherlands [ 16 ].…”
Section: Introductionmentioning
confidence: 99%